2021
DOI: 10.5747/ca.2021.v17.n3.a436
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy in native fruit seeds of the Brazilian South Region

Abstract: The aim of the present study was to investigate whether seeds from six native fruit species ofthe South Brazilian regionhad any type of dormancy, as well as, to verify if they havephotoblastism. The work was carried out at the Plant Physiology Laboratoryofthe Federal Technological University of Paraná –Câmpus Dois Vizinhos, Paraná State, Brazil. The influence of photoperiod factors and techniques for overcoming dormancy were tested on the germination of Eugenia uniflora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Our results are similar to other studies on Eugenia species (Amador and Barbedo, 2015). Eugenia uniflora seeds have no dormancy period and are sensitive to desiccation (Stricker and Stiling, 2013;Pavithra et al, 2020;Pirola et al, 2021). Typically, seeds sensitive to desiccation, which are more common in tropical systems, are larger, have a greater moisture content, and have faster germination rates (Bazzaz and Pickett, 1980;Vázquez-Yanez and Orozco-Segovia 1993;Daws et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to other studies on Eugenia species (Amador and Barbedo, 2015). Eugenia uniflora seeds have no dormancy period and are sensitive to desiccation (Stricker and Stiling, 2013;Pavithra et al, 2020;Pirola et al, 2021). Typically, seeds sensitive to desiccation, which are more common in tropical systems, are larger, have a greater moisture content, and have faster germination rates (Bazzaz and Pickett, 1980;Vázquez-Yanez and Orozco-Segovia 1993;Daws et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Stimulate ® has been used in several crops with satisfactory results regarding shoot growth, as observed for Hymenaea courbaril L. (SMIDERLI et al, 2022). Hormonal treatment in seeds positively contributed to germination and seedling formation of Myrtaceae species (HOSSEINI et al, 2020;PIROLA et al, 2021), which is similar to what was observed for M. glomerata. For seeds of Physalis angulata L., an increase in the first germination count, germination speed index, and seedling formation was observed when seeds were pre-imbibed in Stimulate ® solution 1.50% (SANTIAGO et al, 2019).…”
Section: Methodssupporting
confidence: 68%
“…Similarly, Pirola et al (2021) reported that it is not recommended to use water at 80 ºC and sulfuric acid to overcome the dormancy of seeds of Eugenia uniflora L., Plinia peruviana (Poir.) Govaerts, Plinia cauliflora (Mart.)…”
Section: Discussion Experimentsmentioning
confidence: 99%
“…The seeds of C. guazumifolia present negative photoblastism with morphophysiological dormancy, and using hot water or sulfuric acid in the seeds is not recommended (Pirola et al, 2021). The seeds are recalcitrant, do not support desiccation with short post-harvest longevity, and it is recommended that the seeds be washed with running water, keeping them in a humid place with planting after a short storage time (MIRANDA et al, 2020;MOSER et al, 2022).…”
Section: Propagationmentioning
confidence: 99%